Novel biallelic MCMDC2 variants were associated with meiotic arrest and nonobstructive azoospermia - Hao-Wei Bai; Na Li; Yu-Xiang Zhang; Jia-Qiang Luo; Ru-Hui Tian; Peng Li; Yu-Hua Huang; Fu-Rong Bai; Cun-Zhong Deng; Fu-Jun Zhao; Ren Mo; Ning Chi; et al. (Asian Journal of Andrology)
Nonobstructive azoospermia (NOA), one of the most severe types of male infertility, etiology often remains unclear in most cases. Therefore, this study aimed to detect four biallelic detrimental variants (0.5%) in the minichromosome maintenance domain containing 2 (MCMDC2) genes in 768 NOA patients by whole-exome sequencing (WES). Hematoxylin and eosin (H&E) demonstrated that MCMDC2 deleterious variants caused meiotic arrest in three patients (c.1360G>T, c.1956G>T, and c.685C>T) and hypospermatogenesis in one patient (c.94G>T), as further confirmed through immunofluorescence (IF) staining. The single-cell RNA sequencing data indicated that MCMDC2 was substantially expressed during spermatogenesis. The variants were confirmed as deleterious and responsible for patient infertility through bioinformatics and in vitro experimental analyses. The results revealed four MCMDC2 variants related to NOA, which contributes to the current perception of the function of MCMDC2 in male fertility and presents new perspectives on the genetic etiology of NOA.